Leadership Style as a Catalyst for Change: An Analysis of Its Impacon the Performance and Service of the SAR Office - Heru Suhartono; Arvy N. Osma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Overview of the Object of Research: This study focuses on the organizational performance of the Semarang SAR Office, a public institution under the National Search and Rescue Agency (Basarnas), which plays a strategic role in emergency and disaster response in Indonesia. Problems and Research Objectives: The problem arises from suboptimal organizational performance and service quality during the previous leadership period (2008–2021). The research aims to identify leadership styles that significantly influence improvements in organizational performance and public service delivery, especially following the leadership transition in July 2021. Proposed Methods: This research adopts a qualitative case study approach. Data were collected through interviews, observations, and document analysis involving key personnel within the Semarang SAR Office to explore the practical implementation and outcomes of different leadership styles. Main Findings and Synthesis: Findings show that transformational, servant, and situational leadership styles have positively impacted employee attitudes, institutional responsiveness, and service accountability. There has been a measurable increase in key performance indicators such as SOP development, response time, personnel competence, and service facilities. However, these improvements may also be influenced by other organizational or external factors. Conclusions: Effective leadership plays a critical role in enhancing organizational performance in public service institutions. The study concludes that a leadership approach aligned with organizational culture and employee engagement is essential for sustainable service quality improvements. Continuous and holistic evaluations are necessary to determine the long-term impact of leadership practices.